Convergence of Income in Asian Countries - Lee, Hock Ann (2002)
This study examines convergence of per capita real income for seven Asian countries namely Indonesia, Japan, Korea, Malaysia, the Philippines, Singapore and Thailand during the period 1970-1999. It has been argued that income convergence could be used as one of the criteria to form a single currency area. Utilizing the concepts of deterministic and stochastic convergence, this study uses 3 types of time series techniques, namely the standard ADF test, the Zivot- Andrews endogenously determined break points and the Johansen-Juselius cointegration analysis to test the convergence hypotheses. These time series procedures are able to show whether the convergence hypotheses are supportive of the Slow growth model (deterministic convergence or long run convergence) or augmented So low model (stochastic convergence) or endogenous growth model (divergence). In particular, the empirical findings are presented in two ways. First, convergence between individual country' s log per capita real income and aggregate log per capita real income of the group (relative log per capita real income). Second, convergence between two country's log per capita real income (bivariate differences log per capita real income). The results show that per capita income of Indonesia, Japan, Korea and Malaysia is converging to the aggregate per capita income of the group. However, the findings in bivariate differences log per capita real income show that per capita income of Indonesia, Korea, Malaysia and Singapore are converging toward per capita income of Japan. In addition, the results of Zivot-Andrews endogenously determined break points revealed that the year 1978 which was between the first oil shock (1973-1975) and the second oil shock (1979-1980) was not the cause for concerned. This indicates that supply shock or external shock has minimal impact on Asian's countries growth processes. Overall, this study has shown some initial insights on the possible single currency area among Asian countries based on income convergence hypothesis. This can be explained by the fact that Asian countries is undergoing a relatively high growth potential to converge toward a similar per capita income level either with leading country (Japan) or a group of Asian's countries per capita income. However, it should be noted that income convergence is a necessary condition but not a sufficient determinant to form a single currency area. Thus, a meaningful line of further study could be focused on the achievement of Asian regions against the five keys Maastricht Convergence Criteria namely inflation rate, long term interest rate, exchange rate, debt to GDP ratio and budget deficit to GDP ratio.